HPbI3: A New Precursor Compound for Highly Efficient Solution‐Processed Perovskite Solar Cells. (7th January 2015) - Wang, Feng; Yu, Hui; Xu, Haihua; Zhao, Ni
Abstract : Recently, there have been extensive research efforts on developing high performance organolead halide based perovskite solar cells. While most studies focused on optimizing the deposition processes of the perovskite films, the selection of the precursors has been rather limited to the lead halide/methylammonium (or formamidium) halide combination. In this work, we developed a new precursor, HPbI3, to replace lead halide. The new precursor enables formation of highly uniform formamidium lead iodide (FAPbI3 ) films through a one‐step spin‐coating process. Furthermore, the FAPbI3 perovskite films exhibit a highly crystalline phase with strong (110) preferred orientation and excellent thermal stability. The planar heterojunction solar cells based on these perovskite films exhibit an average efficiency of 15.4% and champion efficiency of 17.5% under AM 1.5 G illumination. By comparing the morphology and formation process of the perovskite films fabricated from the formamidium iodide (FAI)/HPbI3, FAI/PbI2, and FAI/PbI2 with HI additive precursor combinations, it is shown that the superior property of the HPbI3 based perovskite films may originate from 1) a slow crystallization process involving exchange of H + and FA + ions in the PbI6 octahedral framework and 2) elimination of water in the precursor solution state. Abstract : HPbI3 is introduced as a novel precursor to solve the non‐uniformity problem of formamidium lead iodide (FAPbI3 ) perovskite films from one‐step solution‐processed method. Interestingly, the FAPbI3 films exhibit high crystallinity with (110) plane orientation and the corresponding devices yield an average photovoltaic efficiency of 15.4% under 1 sun illumination. Present results demonstrate that precursor engineering is an effective approach to produce perovskites with attractive properties.